The philosophical underpinning of the absorber theory of radiation. (November 2020) - Forgione, Marco
Abstract: The paper considers the absorber theory of radiation by (Wheeler and Feynman 1945) and (Wheeler and Feynman 1949) and advances the idea that the theory is grounded on the philosophical intuition of overall processes. Such intuition consists of having to consider advanced and retarded radiation as well as the interaction between absorbers and emitter. I discuss the discrepancy between microdynamic time-symmetry and the asymmetry of the experimental evidences. In doing so, I consider (Price, 1991)'s reformulation of the theory and argue that it overlooks the philosophical intuition. I then compare the overall process idea with some accounts of holism and ultimately suggest that it also played an important role in Feynman's later works. Highlights: Review of the Absorber theory of radiation by Wheeler and Feynman. Comments on Price's reinterpretation of the theory. Suggestion of a 'holistic' interpretation that emphasizes the time symmetry of the interaction. Comments on the historical importance of the theory with respect to Feynman's later works.